Perception of Building Occupants on the use of Generating Sets - Wahab, A.B (European Scientific Journal, ESJ, 2017)
Poor power supply is a major bottleneck to the technological development of the country and this has forced building occupants to shift to dependence on generating sets of different types and brand which subject its users to myriad of effects. This study was aimed at assessing perception of the users of generators in buildings on the effects associated with its usage in Ibadan Metropolis, Nigeria. The study area was divided into core, transition and suburban residential zones. Multistage and quota sampling techniques were used to select respondents sampled in residential and commercial buildings respectively. Descriptive and inferential statistical techniques were used to analyse data collected. The study showed that 50.29%, 51.19%, 45.90% of residential buildings’ respondents in the core, transition and suburban zone while 56.41%, 43.33% and 42.86% of occupants of commercial buildings in the corresponding core, transition and suburban zone indicated that hearing problem was the most physiological effect that the use of generating sets exposed them to. Cut injuries from the elcetro-mechanical components of generating sets were the most prominent injuries had by the occupants of residential buildings while irritation of the eyes during refueling was the most significant effect had by respondents in the commercial buildings. High cost of fuel and damage to electrical appliances were the most uncomfortable indicator with uncomfortability index of 0.804 and 0.776 in residential and commercial buildings respectively. The study also found that the use of generating sets had caused structional, functional and aesthetical effects on the building elements. It was recommended that there is dire need on the part of government to enhance environmental sustainability by provision of sustainable energy sources to buildings in view of the effects associated with the use of generating sets.